Translation of in vitro-transcribed RNA therapeutics - von der Haar, Tobias; Mulroney, Thomas E.; Hedayioglu, Fabio; Kurusamy, Sathishkumar; Rust, Maria; Lilley, Kathryn S.; Thaventhiran, James E.; Willis, Anne E.; Smales, C. Mark (Frontiers in Molecular Biosciences, 2023)
In vitro transcribed, modified messenger RNAs (IVTmRNAs) have been used to vaccinate billions of individuals against the SARS-CoV-2 virus, and are currently being developed for many additional therapeutic applications. IVTmRNAs must be translated into proteins with therapeutic activity by the same cellular machinery that also translates native endogenous transcripts. However, different genesis pathways and routes of entry into target cells as well as the presence of modified nucleotides mean that the way in which IVTmRNAs engage with the translational machinery, and the efficiency with which they are being translated, differs from native mRNAs. This review summarises our current knowledge of commonalities and differences in translation between IVTmRNAs and cellular mRNAs, which is key for the development of future design strategies that can generate IVTmRNAs with improved activity in therapeutic applications.